Equality in the Informed Consent Process: Competence to Consent, Substitute Decision-Making, and Discrimination of Persons with Mental Disorders. Issue 1 (25th January 2021) - Scholten, Matthé; Gather, Jakov; Vollmann, Jochen
Abstract: According to what we propose to call "the competence model, " competence is a necessary condition for valid informed consent. If a person is not competent to make a treatment decision, the decision must be made by a substitute decision-maker on her behalf. Recent reports of various United Nations human rights bodies claim that article 12 of the Convention on the Rights of Persons with Disabilities involves a wholesale rejection of this model, regardless of whether the model is based on a status, outcome, or functional approach to competence. The alleged rationale of this rejection is that denying persons the right to make their own treatment decisions based on an assessment of competence necessarily discriminates against persons with mental disorders. Based on a philosophical account of the nature of discrimination, we argue that a version of the competence model that combines supported decision-making with a functional approach to competence does not discriminate against persons with mental disorders. Furthermore, we argue that status- and outcome-based versions of the competence model are discriminatory.